The omnivore's dilemma : - Pollan, Michael. (Dial Books, 2009)
In a smart, compelling format with updated facts, plenty of photos, graphs, and visuals, as well as a new afterword and backmatter, The Omnivore’s Dilemma serves up a bold message to the generation that needs it most: It’s time to take charge of our national eating habits—and it starts with you.strong coverage of macroeconomic theory and international trade.